Reassessment of physico-chemical water quality in Setiu Wetland, Malaysia - Suratman, S.; Hussein, A.N.A.R.; Latif, M.T.; Weston, K. (Universiti Kebangsaan Malaysia, 2014)
Setiu Wetland is located in the southern part of South China Sea, Malaysia. This wetland has diverse ecosystems that represent a vast array of biological diversity and abundance in utilizable natural resources. However, there are large scales of aquaculture activities within and nearby the wetland which could threaten the ecosystems of this area. Thus, the main goal of the study was to assess the impact of these activities through the measurement of physico-chemical water quality parameters and then compare this to a previous study carried out in the same study area. The parameters (salinity, temperature, pH, dissolved oxygen, biological oxygen demand and total suspended solids) were monitored monthly at the surface water from July to October 2008. The results showed that the impact of aquaculture activities on the water quality in the area with dissolved oxygen and total suspended solids concentrations were considerably lower than those observed previously. With respect to the Malaysian Marine Water Quality Criteria and Standard, most of the level of parameters measured remained Class 1, suggesting the physico-chemical environment were in line with sustainable conservation of the marine protected areas and marine parks of this wetland area.